Present and Scene: A Poetics of Relation. A Brief Log of Connections Between Pablo Messiez’s Scenic Poetics and Gaston Bachelard’s Aesthetic Theory - Ramos Barroso, Gon (Escritura e Imagen, 2024)
This text relates the scenic and pedagogical practices of the Argentinean creator Pablo Messiez, nourished in their very basis by a profoundly philosophical thought, with part of the aesthetic theory of the French thinker Gaston Bachelard. In the coexistence of both worlds, seeds of thought are born that, we believe, shed light on the field that unites philosophy and theatre. As a result of our attendance to a formative process dictated by the Argentinean creator, in addition to the knowledge of his professional practice on national stages, we will establish the connections between his theoreticalpractical world and Bachelard’s texts.